DERIVATIONAL PROCESS OF SOUTH VARIETY OF NIAS LANGUAGE - Impiani Zagoto (Jurnal Education and Development, 2020)
This study is about derivational affixes and the morphophonemic process of Nias Language south variety which focused on the kinds of derivational affix and how the affixes formed. This research used descriptive-explanative to describe and explain the derivational process of Nias Language south variety. The data of this research was collected through documentary technique while the interview was used to verify the data. The data obtained was analyzed by using Miles and Huberman’s interactive model that is data reduction, data display and then drawing conclusion. The result of the analysis shows that there are thirteen kinds of Nias Language south variety affix: fa-, f-, fa’a-, fo-, fe-, va-, ma-, sa-, so-, mo-, si-, s-, a-; five kinds of infix: -ga-, -ge-, -gi-, -go-, -um-; there are eight kinds of suffix are -sa, -gö, -ö, -i, -ini, -wa, -si, -la and there are four kinds of confix: a-la, a-ta, o-ta, a-wa. Some of the affixes of Nias Language south variety involve process morphophonemic when they are attached to the root words which is consisted of three kinds are the process of phoneme change, the process of phoneme addition, and the process of phoneme omission. The morphophonemic process occurs only in the prefixing and confixing. To help the students in understanding the English derivational morphology easily, it is suggested that the teacher use comparative study between English morphology and this research finding.